Effects of type and concentration of proteins on the recovery of spray-dried sucrose powder - Fang, Zhongxiang; Wang, R.; Bhandari, B. (Taylor & Francis, 2013)
Dairy proteins (whey protein isolate, hydrolyzed whey protein, calcium-caseinate, and hydrolyzed caseinate) and plant proteins (soy protein isolate, pea protein isolate, and rice protein concentrate) were used to spray-dry sucrose, which is difficult to spray-dry due to its stickiness property. Generally, dairy proteins were more effective than plant proteins as they resulted in higher powder recoveries. Rice protein concentrate was demonstrated to be the least effective candidate for spray drying of sucrose. The higher powder recoveries of some sucrose/protein systems were attributed to the higher surface active properties of the proteins, because they preferentially migrate to the surface of the droplets/particle and cover the powder particle surface with a thin-film of non-sticky protein.